FORMATION OF SELF-EDUCATIONAL ACTIVITY ORGANIZATION SKILLS AS A KEY COMPETENCE OF FUTURE SPECIALISTS - Ткаченко, Вадим (SWorldJournal, 2025)
The article is devoted to the study of the current problem of forming skills in organizing self-educational activities as a key competence of modern specialists in the conditions of a rapidly changing information society and knowledge economy. The theore